Analisis Bibliometrik: Perkembangan Penelitian dan Publikasi Kualitas Pelayanan Rumah Sakit Jiwa dalam Tiga Dekade - Ratnawaty, Yenny; Alfatih, Andy; Lionardo, Andries (Universitas Batanghari Jambi, 2024)
This research aims to find out the trend of scientific publications on the topic of mental hospital service quality over the last three decades, including the description of the network structure of previous researchers and their institutions. The approach method used in this research is the bibliometric analysis method. Bibliometric analysis methods are used to provide an overview of the progress and development of knowledge in studying certain research topics. In carrying out bibliometric analysis, this research uses data from journals or articles indexed by Scopus and visualizes it using the VOSviewer application version 1.6.20. Data collection in this study used keywords by entering the query: ((TITLE-ABS-KEY(